THEORETICAL ASPECTS OF CHANGES IN ECONOMIC STRUCTURE - Vitas, Arturas (Ekonomika, 2011)
The aim of the study was to analyze the theoretical essence of economic structure, present the concept of economic activity and compare the classification systems of economic sectors. The author analyzes the composition of an economic structure and compares their classification systems on the national, EU and world levels. Changes in the economic structure of the Baltic States are also evaluated. The analysis is performed using the data valuation, grouping and comparison methods. The obtained results are summarized and presented in conclusions.